Toward an Energy Efficient Wastewater Treatment: Combining a Microbial Fuel Cell/Electrolysis Cell Anode With an Anaerobic Membrane Bioreactor - Kocatürk-Schumacher, Nazli Pelin; Madjarov, Joana; Viwatthanasittiphong, Pavaris; Kerzenmacher, Sven (Frontiers in Energy Research, 2018)
Recently, it has been shown that combining a bioelectrochemical system (BES) with an anaerobic membrane bioreactor (AnMBR) to produce electricity can reduce the overall energy consumption of wastewater treatment. In this study, we tested the recently proposed concept that integrates a microbial anode into an AnMBR, under application relevant conditions, for the treatment of synthetic brewery wastewater. We developed two system configurations: a filtering anode with stainless steel filter plate; and a hybrid anode, in which a polymeric membrane is combined with stainless steel mesh. As fouling is problematic in AnMBRs, we investigated the effect of two fouling mitigation methods, namely electrochemical cleaning and application of a turbulence promotor, on the permeate fluxes and current densities. We also investigated the effect of cathode (counter electrode) position on the permeate fluxes and current densities in filtering and hybrid anode. Our results revealed that permeate fluxes were influenced by the membrane pore size; and dropped below 5 L m−2 hr−1 on day 3 with filter grade 0.5 μm; whereas similar values of permeate flux were observed after 5 days of operation with the membrane with filter grade 0.1 μm. COD removal across the membrane reached up to 644 mg L−1 indicating improvement in energy efficiency and effluent quality of the AnMBR. The location of cathode did not influence permeate fluxes and current densities, but permeate pH was largely affected. Electrochemical cleaning improved permeate fluxes more than 2-fold (18.9 L m−2 hr−1 after 7 days of operation) compared to the operation of the 0.1 μm membrane without a cleaning procedure. Application of a turbulence promotor increased permeate fluxes and current densities in filtering anode. The hybrid anode resulted in similar current densities, but higher permeate fluxes as compared to the filtering anode, which dropped below 20 L m−2 hr−1 only after 8 days of operation. The hybrid anode configuration is an attractive option that combines high permeate fluxes on conventional non-conductive filters with current generation on an inexpensive conductive material. In summary, our results demonstrate that combining BES with AnMBR is a promising approach toward an energy efficient wastewater treatment.